LEGAL CERTAINTY ARTICLE 15 PARAGRAPH (3) LAW NUMBER 2 OF 2014 CONCERNING AMENDMENT TO LAW NUMBER 30 OF 2004 CONCERNING NOTARIES - Rubby Aditya Panglima; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
This study discusses the ambiguity of norms in Article 15 paragraph (3) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notaries (Amendments to the Notary Law) which affect legal certainty in the regulation of the authority of a notary related to